Coupled bending-torsion behaviour of single-box multi-cell curved composite box-girders with corrugated-steel-webs. (September 2022) - Wang, Can; Zhang, Yanling; Zhang, Xu; Li, Yunsheng; Wei, Xinxin
Abstract: Due to initial curvature, curved composite box-girder with corrugated steel webs (CCBG-CSWs) exhibits complex behaviour. This study develops an analytical solution for describing coupled bending-torsion behaviour of CCBG-CSWs with arbitrary single-box multi-cell cross-section in elastic stage under arbitrary loads. First, governing differential equations are deduced with energy-variational principle and solved by Galerkin-method. Next, experimental studies and finite element analysis are performed, which validates the analytical solution. It also identifies governing parameters. Discussion of analytical solution's calculated items shows steel webs' shear deformation has significant effects on flexural deflection, but no effects on torsional angle and normal stress at section corner. The additional restrained torsion has little impact on flexural deflection and torsional angle while non-negligible influence on normal stress. Shear lag effect of flanges has larger effects on the normal stress than that of on the flexural deflection and torsional angle. Furthermore, parametric study presents span-radius ratio and bending-torsion stiffness ratio have substantial impacts on bending-torsion behaviour. The corrugated steel web thickness and the eccentricity between torsional centre and centroid have relatively less effects. Diaphragm spacing effects are the least. The study may provide new insights to understand the coupled bending-torsion behaviour of CCBG-CSWs and finally guide better design. Highlights: An analytical solution is developed to describe the coupled bending-torsion behaviour of CCBG-CSWs. Governing differential equations are deduced with energy-variational principle and solved by Galerkin-method. Both experimental studies and finite element analysis are performed to validate the analytical solution. Governing parameters are identified for the coupled bending-torsion behaviour of CCBG-CSWs.